2001
DOI: 10.1038/sj.jea.7500171
|View full text |Cite
|
Sign up to set email alerts
|

Use of expert judgment in exposure assessment. Part I. Characterization of personal exposure to benzene

Abstract: This paper presents the results of the first phase of a study, conducted as an element of the National Human Exposure Assessment Survey ( NHEXAS ) , to demonstrate the use of expert subjective judgment elicitation techniques to characterize the magnitude of and uncertainty in environmental exposure to benzene. In decisions about the value of exposure research or of regulatory controls, the characterization of uncertainty can play an influential role. Classical methods for characterizing uncertainty may be suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…Part I of this study (Walker et al, 2001 ) demonstrated that, using principles of good elicitation practices, coherent probability distributions about levels of benzene in ambient, indoor, and personal air in U.S. EPA's Region V could be elicited from experts in this field. In the absence of appropriate measurement data, their probability judgments about the mean and 90th percentiles of benzene in ambient, indoor and personal air in Region V could be used as inputs to discussions about the appropriate level of regulatory concern about current levels of benzene or to decisions about the value and focus of future monitoring programs for benzene.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Part I of this study (Walker et al, 2001 ) demonstrated that, using principles of good elicitation practices, coherent probability distributions about levels of benzene in ambient, indoor, and personal air in U.S. EPA's Region V could be elicited from experts in this field. In the absence of appropriate measurement data, their probability judgments about the mean and 90th percentiles of benzene in ambient, indoor and personal air in Region V could be used as inputs to discussions about the appropriate level of regulatory concern about current levels of benzene or to decisions about the value and focus of future monitoring programs for benzene.…”
Section: Discussionmentioning
confidence: 98%
“…The judgments calibrated in this paper are the experts' predictions about the mean and 90th percentile of the residential ambient, residential indoor, and personal air concentrations ( exposure ) in EPA Region V. As discussed in detail in Part I of our study, seven experts knowledgeable about various facets of benzene personal exposure were chosen through a peer-nomination process, attended a group workshop to discuss the project and data relevant to the questions, and participated in a formal elicitation of their individual judgments ( Walker et al, 2001).…”
Section: The Judgmentsmentioning
confidence: 99%
See 3 more Smart Citations